Evaluation of the Efficacy of the Brucella canis RM6/66 ΔvjbR Vaccine Candidate for Protection against B. canis Infection in Mice - Lauren W. Stranahan; Sankar P. Chaki; Daniel G. Garcia-Gonzalez; Omar H. Khalaf; Angela M. Arenas-Gamboa (mSphere, 2020)
ABSTRACT Brucella canis is a Gram-negative, facultative intracellular bacterium and the causative agent of canine brucellosis, a highly contagious disease of dogs that can be transmitted to humans. Unfortunately, no vaccine is available to prevent infection. We recently characterized the kinetics of B. canis infection in the mouse model, establishing the required dose necessary to achieve systemic infection. The objective of this study was to investigate the utility of the mouse model in assessing canine brucellosis vaccine candidates and to subsequently investigate the safety and efficacy of a live attenuated vaccine, the B. canis RM6/66 ΔvjbR strain. Mice vaccinated with a dose of 109 CFU of the vaccine strain by both intraperitoneal and subcutaneous routes were afforded significant protection against organ colonization and development of histopathologic lesions following intraperitoneal challenge. Addition of an adjuvant or a booster dose 2 weeks following initial vaccination did not alter protection levels. Vaccination also resulted in a robust humoral immune response in mice, and B. canis RM6/66 ΔvjbR was capable of activating canine dendritic cells in vitro. These data demonstrate that the B. canis RM6/66 ΔvjbR strain shows promise as a vaccine for canine brucellosis and validates the mouse model for future vaccine efficacy studies. IMPORTANCE Canine brucellosis, caused by Brucella canis, is the primary cause of reproductive failure in dogs and represents a public health concern due to its zoonotic nature. Cases in dogs in the United States have been increasing due to the persistent nature of the bacterium, deficiencies in current diagnostic testing, and, most importantly, the lack of a protective vaccine. Current estimates place the seroprevalence of B. canis in the southern United States at 7% to 8%, but with the unprecedented rates of animals moving across state and international borders and the lack of federal regulations in regard to testing, the true seroprevalence of B. canis in the United States may very well be higher. Vaccination represents the most effective method of brucellosis control and, in response to the demand for a vaccine against B. canis, we have developed the live attenuated B. canis RM6/66 ΔvjbR vaccine strain capable of protecting mice against challenge.